The future and the role of human resource management in South Africa during the Fourth Industrial Revolution - Cecilia M. Schultz (SA Journal of Human Resource Management, 2021)
Orientation: The world of work is evolving at an alarming rate, and human resource (HR) practitioners need to familiarise themselves with the future of human resource management (HRM) in order to add value to their organisations.